Design of Novel STASOSM Controller for FOC Control of Dual Star Induction Motor Drives - Pham, Ngoc Thuy (Association for Scientific Computing Electronics and Engineering (ASCEE), 2024)
In this paper, a Novel Super-Twisting Algorithm combined with Improved Second - Order Sliding Mode (NSTASOSM) for the Field-Oriented Control (FOC) of high performance SPIM drives is proposed. This structure, on the one hand, effectively solves the weaknesses of traditional backstepping control (BS) and sliding mode (SM) control that are the dependent on the change of parameters, load disturbance and the phenomenon of chattering, on the other hand, increases the convergence speed and the reference tracking ability, enhance the robust and stably of drive systems even when working in conditions of uncertain parameter and load disturbances, eliminates the chattering phenomenon. The obtained results by simulation using the Matlab/ Simulink tool verified the performance of this proposed control structure.